(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article explores the linguistic intricacies involved in translating film subtitles between English and Uzbek languages. It delves into the challenges faced by translators, such as navigating cultural nuances, adapting idiomatic expressions, and maintaining consistency in character voices. The article emphasizes the importance of cultural sensitivity, creative adaptation for humor and wordplay, and addressing technical constraints in achieving effective subtitle translations. By examining these linguistic features, the annotation highlights the complexities of the translation process and underscores the necessity of skilled linguists to ensure a seamless and culturally resonant viewing experience for audiences in both English and Uzbek-speaking communities.